64-slice single source CT와 128-slice dual source CT를 이용한 관상동맥 조영 검사 시 환자선량 비교 - 강영한; Yeonghan Kang (Journal of the Korean Society of Radiology, 2012)
본 연구는 64-절편 단선원 CT(SSCT)와 128-절편 이중선원(DSCT)을 이용한 관상동맥조영 CT 검사 시 방사선량에 대해 알아보고, 이 선량으로 인한 암 발생의 잠재적 위험(LAR)을 평가해 보았다. SSCT의 후향적동조화(RGH)스캔의 유효선량은 13.86 mSv 이었고, DSCT의 RGH 스캔의 유효선량은 11.87 mSv 이었다. DSCT의 전향적동조화 (PGT) 스캔 중 선량변조를 적용치 않은 모드의 유효선량은 5.61 mSv, 선량변조를 적용하였을 때는 3.04 mSv 이었다. 1회 스캔하는 FLASH 모드는 0.98 mSv 이었다. SSCT의 RGH 스캔의 LAR은 1,176명 중 1명, DSCT의 RGH에서는 1,960명 중 1명이었다. DSCT의 PGT는 3,030명 중 1명, 선량변조를 하면 5,882명 중 1명에서 발암 위험이 있었다. 따라서 SSCT와 DSCT를 이용한 관상동맥조영 CT 검사는 암발생 귀속위험과 관련성이 있음을 인지하여야 하고, 환자 선량을 줄이기 위해 RGH보다 PGT, FLASH 등의 프로토콜을 적용하는 것이 필요하다. The purpose of this study was to estimate radiation doses from 64-slice single source Computed Tomography(SSCT) coronary angiography(CA) and 128-slice dual source Computed Tomography(DSCT). With SSCT CA, the effective dose averaged approximately 13.86 mSv when two dose modulation was not. The mean effective dose for DSCT CA with retrospectively gated helical(RGH) technique was 11.87 mSv, when prospective ECG gating transverse(PGT) without dose modulation technique was 5.61 mSv. The one with dose modulation in PGT technique and flash mode were 3.04 mSv and flash mode was 0.98 mSv respectively. The lifetime attributable risk(LAR) of cancer incidence from SSCT RGH mode averaged approximately 1 for 1,176, and DSCT averaged 1 for 1,960(RGH mode), 1 for 3,030(PGT without modulation), 1 for 5,882(PGT with modulation). Because of CTCA is associated with non-negligible risk of cancer. Doses can be reduced by application PGT, FLASH than RGH using DSCT.